Predictors of Prolonged Hospital Stay Among Pediatric Patients With Severe Pneumonia, Southwest Ethiopia: Prospective Follow-Up Study - Belete Fenta Kebede; Yalemtsehay Dagnaw Genie; Tsegaw Biyazin Tesfa; Aynalem Yetwale Hiwot; Kassa Kindie Mulu; Emebet Adugnaw; Esmelalem Mihretu; Enatfenta Sewmehone Endalew (SAGE Publishing, 2024)
Background Prolonged hospital stay could lead to increased hospital-acquired infections, and unnecessary utilization of hospital beds, medications, and other resources. However, there is limited evidence regarding the length of hospital stay (LOS) and predictors of prolonged hospital stay in pediatric patients with severe pneumonia. Therefore, this study was conducted to fill the information gap on length of stay and predictors of prolonged hospital stay among pediatric patients with severe pneumonia, in southwest Ethiopia. Objective This study aimed to determine the LOS and predictors of prolonged hospital stay among pediatric patients with severe pneumonia, Southwest Ethiopia/2022. Methods and Materials A Prospective follow-up study was conducted on pediatric patients with severe pneumonia. Data were entered into Epi-data manager Version 4.4.2.1, for coding, editing, and cleaning, then exported to Stata Version 16 for analysis. Bivariate logistic regression analysis at a significance level of 0.25 and multivariate logistic regression analyses with a significance level of 0.05 were conducted to determine the factors associated with prolonged hospital stay among pediatric patients. Results In this study, the median LOS was 5 days and, approximately 38.22% (95% CI [33.66-43.01]) of patients with severe pneumonia had prolonged hospital stays. The presence of underlying comorbidity (adjusted odds ratio [AOR]: 2.64, 95% CI [1.65-4.26]), health insurance status (AOR: 2.22, 95% CI [1.4-3.55]), and incomplete vaccination status (AOR: 4.20, 95% CI [1.04-16.61]) were independent predictors of prolonged hospital stay among pediatric patients with severe pneumonia. Conclusion In this study, more than one-third of pediatric patients with severe pneumonia had a length of stay of more than 5 days, and incomplete vaccination status, insurance status, and underlying comorbidities were independent predictors of prolonged hospital stay. Therefore, healthcare providers, parents, and other stakeholders should work to improve the pneumococcal vaccination rate, timely initiation of advanced diagnosis, and patient management of comorbid diseases to reduce hospital stays for pediatric patients with severe pneumonia.